The Inhibiting Process of the Enterococcus Faecalis Growth using Coffea Arabica Extract - Pohan, Dame Joyce; Silaban, Hertina (Eximia, 2023)
Arabica coffee seeds contain caffeine, chlorogenic acid, flavonoids, and trigonelline. This study aims to test the antibacterial of Arabica coffee seed extract against the bacterium Enterococcus faecalis at concentrations of 1,5625%, 3,125%, 6,25%, 12,5%, 25%, 50%, and 100%. The extraction method uses maceration with solvent 96%. The Kirby and Bauer diffusion test used the antibacterial activity test method. The results showed that mango seed extract could provide inhibition starting from 3,125% with an average diameter of inhibition zone of 1,16 mm to the largest concentration of 100% with an average zone diameter of inhibition of 14,6 mm. At the same time, the average diameter of the inhibitory zone of antibiotic ampicillin at a concentration of 1% as a control (+) is 24,6 mm. The results showed that the greater concentration, the greater the inhibitory zones are formed.